Hot Off the Press: Chemical Versus Electrical Cardioversion for Atrial Fibrillation. (24th November 2019) - Bond, Christopher; Morgenstern, Justin; Heitz, Corey; Milne, William K.
Abstract: Atrial fibrillation (AF) is a significant dysrhythmia that often requires treatment in the emergency department (ED). This can be performed with rhythm control using electrical or chemical cardioversion or with rate control. There is widespread variation in management of AF within Canada and worldwide. This study focuses on rhythm control techniques, comparing ED length of stay when using an electrical‐first strategy versus a chemical‐first strategy of cardioversion.